COVID-19 pandemic's impact on the labour market in ASEAN countries - Li, Jingyi; Lim, Beatrice; Pazim, Khairul Hanim; Furuoka, Fumitaka (AEI Insights, 2021)
This paper aims to examine the impact of the COVID-19 pandemic on the labour market in ten ASEAN countries, namely Brunei, Lao PDR Cambodia, Indonesia, Malaysia, the Philippines, Myanmar, Singapore, Vietnam and Thailand. A flu virus first detected in China later affected neighbouring Southeast Asian countries. Although the pandemic has varying implications and at varying levels, it has a negative impact on the ASEAN economies. The labour market is affected as economic activities came to a halt when ASEAN governments-imposed lockdowns or restricted movement. Job losses continue to escalate amid the pandemic, vulnerable workers such as those working in informal sectors, self-employed workers, gig workers, migrant workers, and micro, small and medium enterprises are facing a tough labour market and also at risk of losing livelihood due to lockdown. Post-COVID-19, ASEAN region sees the need for collective action to build the economy, leveraging on technology and digital trade. The pandemic may reshape ASEAN’s digital landscape in the labour market especially on the way work is done in the future.